Pathways from child sexual and physical abuse to sexual and physical intimate partner violence victimization through attitudes toward intimate partner violence - Schuster, Isabell (Journal of family violence, 2021)
Although many studies have shown that victims of child abuse have an increased vulnerability to revictimization in intimate relationships, the underlying mechanisms are not yet sufficiently well understood. Therefore, this study aimed at examining this relationship for both sexual and physical forms of violence as well as investigating the potential mediating role of attitudes toward sexual and physical intimate partner violence (IPV). Also, the potential moderating role of gender was explored. Sexual and physical child abuse and IPV victimization in adulthood as well as attitudes toward the respective form of IPV were assessed among 716 participants (448 female) in an online survey. The path analyses showed that child sexual abuse was positively linked to sexual IPV victimization among both women and men, whereas child physical abuse was positively associated with physical IPV victimization among women only. Furthermore, the relationship between both forms of child abuse and IPV victimization was mediated through more supportive attitudes toward the respective forms of IPV, but only among men. This study provides novel insights regarding the links between sexual and physical child abuse and revictimization in adulthood, suggesting that supporting attitudes toward IPV may be seen as vulnerability factor for revictimization. The moderating role of gender is especially discussed.